Identification of Acid Mine Drainage Microorganisms from a Coal Mine in South Africa - Deenanath, Evanie Devi; Falcon, Rosemary (International Journal of Biotechnology for Wellness Industries, 2016)
Acid mine drainage (AMD) generated from mining processes is an on-going environmental concern. This study aimed to identify microorganisms (MOs) from a coal mine water source to determine organism diversity for its use as a bioremediation method of AMD contaminated sources. For the purpose of this study, a culture-dependent sample, previously collected from an open-mine-water-pit was used to assess the microbial community by 18S rRNA gene amplification and BLAST analysis. The analysis revealed the presence of 94 MOs, with 3 dominant MOs namely, Cercozoan; an uncultured bacterium and Chorella vulgaris. The use of this culture is not promising as the presence of Cercozoan, a protist type body will target other species for its own survival, hence inhibiting any positive effect the algae or bacteria may have on bioremediation potential of harmful AMD elements.